1992
DOI: 10.1128/jvi.66.3.1635-1640.1992
|View full text |Cite
|
Sign up to set email alerts
|

GLVR1, a receptor for gibbon ape leukemia virus, is homologous to a phosphate permease of Neurospora crassa and is expressed at high levels in the brain and thymus

Abstract: The human gene GLVR1 has been shown to render mouse cells sensitive to infection by gibbon ape leukemia virus. This indication that the GLVR1 protein acts as a virus receptor does not reveal the protein's normal physiological role. We now report that GLVR1 is homologous to pho-4', a phosphate permease of Neurospora crassa, at a level sufficiently high to predict that GLVR1 is also a transport protein, although the substrate transported remains unknown. To characterize the gene further, we have cloned cDNA for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
83
0

Year Published

1993
1993
2009
2009

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 136 publications
(83 citation statements)
references
References 28 publications
0
83
0
Order By: Relevance
“…In 2002 Farrell et al proposed a PiT1 membrane topology model, which is based primarily on TM predictions by PHD but also leans on PiT2 glycosylation data obtained by Salau¨n and coworkers [41]. For the N-terminal three-fourths of PiT2 (residues 1-483) and PiT1 (residues 1-511) the topological models suggested by both groups comprise seven N-terminal TM domains (I to VII) preceding the large intracellular domain (TM IV was not predicted by Johann et al [22]) ( Fig. 7).…”
Section: Discussionmentioning
confidence: 91%
See 2 more Smart Citations
“…In 2002 Farrell et al proposed a PiT1 membrane topology model, which is based primarily on TM predictions by PHD but also leans on PiT2 glycosylation data obtained by Salau¨n and coworkers [41]. For the N-terminal three-fourths of PiT2 (residues 1-483) and PiT1 (residues 1-511) the topological models suggested by both groups comprise seven N-terminal TM domains (I to VII) preceding the large intracellular domain (TM IV was not predicted by Johann et al [22]) ( Fig. 7).…”
Section: Discussionmentioning
confidence: 91%
“…The spatial [41]. The numbering of the corresponding TM regions predicted by Johann et al [22] is shown in parentheses (TM1-TM10; N.P., not predicted); the N-and C-terminal ends were predicted to be intracellular in this model. The TMs predicted by Johann et al [22], Salaü n et al [23], Farrell et al [41], and PHD at the PredictProtein Server (data not shown) differ in their exact positions.…”
mentioning
confidence: 76%
See 1 more Smart Citation
“…Gibbon ape leukemia virus (GALV) and the closely related simian sarcoma associated virus (SSAV), as well as feline leukemia virus subgroup B (FeLV-B) cross-interfere with one another and belong to receptor group 5. The gene that encodes this receptor, termed GLVRl, has been isolated and shown to resemble a phosphate permease (Johann et al, 1992;O'Hara et al, 1990;Takeuchi et al, 1992) (Table I).…”
Section: Retroviral Interference/superinfection Immunitymentioning
confidence: 99%
“…On the basis of these criteria, three retroviral receptors have been identified and include the well-characterized CD4 molecule, for human immunodeficiency viruses types 1 and 2 (HIV-1 and HIV-2) and simian immunodeficiency viruses (SIVs) Dalgleish et al, 1984;Klatzmann et al, 1984;Maddon et al, 1986;; a basic amino acid transporter termed ecoR or Rec-1, which serves as a specific receptor for the ecotropic murine leukemia viruses (MuLV-E) (Albritton etal., 1989;Kim etal., 1991;Wang etal., 1991a,b); and the GLVRl gene product, which serves as a receptor for gibbon ape leukemia virus (GALV) (O'Hara et al, 1990), the homologous simian sarcoma-associated virus (SSAV), and feline leukemia virus subgroup B (FeLV-B) (Takeuchi et al, 1992). GLVRl also shares homology with a phosphate permease of Neurosporu c r a~~a (Johann et al, 1992).…”
Section: Introductionmentioning
confidence: 99%